Художня часографія прозових творів Костя Гордієнка - Шарова, Тетяна; Sharova, Tetayna (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті увагу зосереджено навколо художньої часографії прозових творів Костя Гордієнка. Наголошено на тому, що прозаїк-Гордієнко є послідовним у своїй творчості: певний ряд тем, ідей, образів формує його світогляд. Однак проза письменника, яка акумулювала моральний досвід війни, свідчить про виняткову згуртованість народу, розкриває торжество людяності навіть там, де напруга й жорстокість двобою не лишали для неї місця. The article focuses around art chasografiya artistic prose. Emphasized that the writer-Gordienko is consistent in his work: a series of themes, ideas, images, shapes his worldview. However, prose writer who has accumulated moral experience of war, shows exceptional unity of the people, reveals the triumph of humanity, even where tensions and violence are not left to fight for her place. Motive impetuosity current time or feature is most evident in the works of Kostya Gordienko about love, his father's house, earnings, hostilities and beloved village. The article states that, as time itself, almost all the characters works the writer's tragic fate. But it does not deprive them of their commitment to life, by contrast, depth of feelings determines the height of each life, fills a special destiny substantial. Bone Gordienko in works of art is presented as a tireless seeker of artistic truth experimenter. He was not peculiar to any concerns or creative stops.
Art Chasohrafiya Prose Kostya Gordienko
Keywords: художня часографія; час; художня творчість; простір; art chasografiya; time; space; arts